Peran dan Mutu Pelaksanaan Pembelajaran oleh Guru di Satuan Pendidikan Tingkat Atas - Zulhafizh, Zulhafizh (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2021)
The purpose of research to analyze the implementation of the role and the quality of learning carried out by teachers in upper-level education units. This research uses descriptive correlation method. The research sample consisted of 142 people who were spread across several upper level education units in Siak Regency, Riau Province. The instrument used for data collection was a Likert scale questionnaire. The analysis technique uses descriptive statistics, Product Moment correlation, normality, and anova. The results showed that all the actions taken had a significant role, namely reaching 47.8%, while 52.3% was determined by other factors. All activities carried out have an influence on the form of learning. The implementation of learning carried out in the upper level education unit has a very high quality standard. The teachers have taken appropriate actions to achieve learning objectives. The ability and skills of teachers in carrying out their duties are a means of realizing productive learning.